Improving Teacher Discipline and Performance through Leadership Analysis of the Head of Madrasah Aliyah - Anis Fauzi; Hanafi Hanafi; Irman Suherman; R. Siti Fauziah; Durotun Nasihah; Rifyal Ahmad Lugowi (STAI Hubbulwathan Duri, 2025)
This study investigates the leadership practices of madrasah heads in enhancing teacher discipline and performance at Madrasah Aliyah in Cilegon City, Indonesia. A qualitative research approach was employed, utilizing observations, interviews, documentation, triangulation, field notes, and member checks to gather data. The analysis involved qualitative techniques supported by data processing to calculate average response scores from various respondent groups. The findings reveal a positive trend in teacher discipline and performance at Madrasah Aliyah in Cilegon City. Key leadership practices contributing to this improvement include routine attendance checks, weekly evaluations, briefings, and addressing disciplinary issues during staff meetings. However, at Madrasah Aliyah Negeri 1 and Negeri 2, the leadership’s impact has been limited. This is attributed to the continuation of previous leadership’s programs, with only minimal introduction of new initiatives. While leadership practices have contributed to improved teacher performance across the madrasahs, their effectiveness varies. The continuation of outdated work programs without significant innovation has hindered leadership effectiveness in certain institutions.